Phospholipase C activation induced by noradrenaline in rat hippocampal slices is potentiated by GABA-receptor stimulation. - Ruggiero, M (1987)
We have studied the effect of gamma-aminobutyric acid (GABA) and other GABA-receptor agonists (3-aminopropanesulphonic acid and muscimol) on the noradrenaline-induced stimulation of polyphosphoinositide metabolism in rat hippocampal slices. Formation of water-soluble inositol phosphates, and polyphosphoinositide metabolism were studied in hippocampal slices prelabelled with [3H]myoinositol. Noradrenaline induced formation of inositol mono-, bis- and trisphosphate during 10 min incubation in the presence of lithium; activation of phospholipase C by noradrenaline was also reflected by the hydrolysis of polyphosphoinositides and by the increased metabolism of phosphatidylinositol. GABA-receptor agonists were unable to activate per se phospholipase C; however, when added together with a low concentration of noradrenaline, they greatly potentiated the noradrenaline-stimulated polyphosphoinositide metabolism. We conclude that GABA-receptor agonists potentiate the effect of noradrenaline on polyphosphoinositide turnover and we discuss the role of this neurotransmitter interaction in the physiology of the hippocampus.